SCIENTIFIC TREASURE OF ACADEMICIAN P.M. VASILYENKO - Іванишин, В. В.; Войтюк, Д. Г.; Деркач, О. П. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
A characteristic feature of the modern Ukrainian society is the growing interest in the history of science and technology, in particular, in the scientific, educational and organizational activities of prominent Ukrainian scholars who selflessly worked for the development of science and education in Ukraine. In recent years, studies have been published covering the development of science and education, including technical, through the study and reflection of the scientific, educational and social activities of a prominent individual. One of these personalities was Petro Vasilyenko - Academician of the National Academy of Agrarian Sciences, Corresponding Member National Academy of Sciences of Ukraine, Academician of the Russian Academy of Agricultural Sciences, Doctor of Technical Sciences, Professor. In the fields of agricultural mechanics, agricultural engineering, mechanization, electrification and automation of agricultural production in Ukraine, he had the achievement of a world-class level that glorified domestic science far beyond the borders of the country. He was rightly called the leader of the agricultural mechanics of Ukraine